Electric‐Field‐Controlled Antiferromagnetic Spintronic Devices. Issue 12 (11th February 2020) - Yan, Han; Feng, Zexin; Qin, Peixin; Zhou, Xiaorong; Guo, Huixin; Wang, Xiaoning; Chen, Hongyu; Zhang, Xin; Wu, Haojiang; Jiang, Chengbao; Liu, Zhiqi
Abstract: In recent years, the field of antiferromagnetic spintronics has been substantially advanced. Electric‐field control is a promising approach for achieving ultralow power spintronic devices via suppressing Joule heating. Here, cutting‐edge research, including electric‐field modulation of antiferromagnetic spintronic devices using strain, ionic liquids, dielectric materials, and electrochemical ionic migration, is comprehensively reviewed. Various emergent topics such as the Néel spin–orbit torque, chiral spintronics, topological antiferromagnetic spintronics, anisotropic magnetoresistance, memory devices, 2D magnetism, and magneto‐ionic modulation with respect to antiferromagnets are examined. In conclusion, the possibility of realizing high‐quality room‐temperature antiferromagnetic tunnel junctions, antiferromagnetic spin logic devices, and artificial antiferromagnetic neurons is highlighted. It is expected that this work provides an appropriate and forward‐looking perspective that will promote the rapid development of this field. Abstract : Antiferromagnetic materials are promising for next‐generation ultrafast, high‐density, and magnetic‐field‐insensitive spintronic device applications. However, unlike ferromagnets, the spin states of antiferromagnets are challenging to modulate. Various electric‐field approaches, which have shown great potential for harnessing spins in antiferromagnets and are of ultralow power owing to Joule heating suppression, are comprehensively reviewed.